Pelatihan Menggambar 3D dengan Software Sketchup untuk Meningkatkan Kompetensi Siswa dan Siswi SMKN 2 Pekanbaru - Muthia Anggraini; Virgo Trisep Haris; Alfian Saleh (Jurnal Pengabdian KOLABORATIF, 2025)
Vocational High Schools are schools in the realm of secondary-level education to prepare students who are ready to work in certain fields. To improve the student competency skills (soft skills) in 3D drawing, the students of SMKN 2 Pekanbaru can be provided with drawing training using the Sketchup program. SMKN 2 Pekanbaru has 12 skills programs, namely construction and housing engineering, modeling design and building information, mechanical engineering, automotive engineering, analytical chemistry, industrial chemical engineering, electronics engineering, welding and metal fabrication engineering, geospatial engineering, software and game development, electrical engineering, computer network engineering, and telecommunications. SketchUp is a 3D graphic design program owned by Google. This application is usually used by civil engineering professionals, architects, or designers in creating 3D designs related to building design, architectural design work, game creation, and related matters. 3D drawing training for SMKN 2 Pekanbaru students aims to improve students' competency and soft skills in the field of 3D drawing. The methods used are the telling method, practice, and evaluation stage. As a result, the students of SMKN 2 Pekanbaru were enthusiastic about receiving this training, where 100% of the participants understood the material provided.